Patrimoine géologique : conservation et valorisation in situ des fossiles. Trente années d’expérimentation en Haute-Provence - Myette Guiomar (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The Nature Reserve of Haute-Provence was one of the first geological Reserves in France to propose permanent in situ exhibit of fossils. Left outdoor or enclosed under a protective cover, the fossils and their geological support raise problems for their conservation. The present article proposes a critical look on what the Reserve experimented in this domain for more than thirty years.